2019
DOI: 10.33899/ijvs.2019.163244
|View full text |Cite
|
Sign up to set email alerts
|

The impact of melatonin administration on the fertility performance and several relating parameters during the breeding season in the Arabi ewes

Abstract: A total of twenty-four healthy ewes aged between 2-3 years old and weighed about 35.09 kg of body weight were divided randomly into four groups (6 animals for each group). The first group included the non-treated control group, while the other three groups were subjected to various oral doses of melatonin 9 mg, 12 mg and 15 mg/head, respectively. All treatments were applied at 6 o'clock in the morning, to investigate the effect of treatment with melatonin during breeding season on reproductive performance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Treatment of ewes with melatonin improved the reproductive performance of domestic ewes by increasing the fertility rate and the number of additional pregnancies [67]. As Kassim et al [68] noted, Melatonin treatment at doses 12 and 15 mg/ head showed an increase in the percentage of fertility and twinning in ewes.…”
Section: The Use Of the Melatonin Hormonementioning
confidence: 92%
“…Treatment of ewes with melatonin improved the reproductive performance of domestic ewes by increasing the fertility rate and the number of additional pregnancies [67]. As Kassim et al [68] noted, Melatonin treatment at doses 12 and 15 mg/ head showed an increase in the percentage of fertility and twinning in ewes.…”
Section: The Use Of the Melatonin Hormonementioning
confidence: 92%
“…The pregnancy rate results agreed with the earlier reports (16, 17, 42) when buffaloes were treated with melatonin, in injectable or slowrelease forms, during the low breeding season. Previous reports proved that melatonin administration improved fertility and fecundity in ewes (49)(50)(51). A higher percentage of pregnancy rates might be associated with an improvement in fertilization which is connected to the antioxidant capacity of melatonin (52).…”
Section: Interval Between 2ndmentioning
confidence: 94%
“…However, melatonin synthesis involves the conversion of hydroxylated tryptophan to 5-hydroxytryptophan, which is then converted into serotonin. This process also controls ovarian activity in seasonal animals, such as cats (Al-Hamedawi T M et al, 2020;AL-Shammary and Al-Yasiri, 2023), with peak concentrations occurring during anestrus and interestrus (Kassim et al, 2019). Exogenous melatonin (administered orally or by injection) appears to suppress cats' estrus cycles.…”
Section: Introductionmentioning
confidence: 99%